Isomorphic Pressures, Top Management Support, and Human Resource Information System (HRIS) Adoption: A Symmetric and Asymmetric Approach - Elizabeth Annan-prah; Joshua Addo; Michael Fudzi; Alfred Andoh (Golden Ratio of Human Resource Management, 2026)
This study examines external pressures, or isomorphic pressures, that influence organizations to adopt HRIS, considering the mediating role of top management support. Using selected public and private organizations in the Central Region of Ghana, a total of 209 responses were collected for analysis. Both symmetric (PLS-SEM) and asymmetric (fsQCA) approaches were employed to examine how isomorphic pressures and TMS predict HRIS adoption. The PLS-SEM results show that coercive and normative pressures predict HRIS adoption and are partially mediated by TMS. The fsQCA results further identify combinations of pressures and TMS that equally predict HRIS adoption. This study supports the extant, consistently conclusive evidence on the relevance of TMS to successful adoption. Additionally, managers can leverage the pressures necessary for adoption decisions in the appropriate conditions.